Myeloma Multipel pada Pasien dengan Fraktur Patologis: Laporan Kasus - I Putu Agni Rangga Githa; Anak Agung Davyn Anantha Rheja (DiscoverSys Inc., 2022)
Background: Multiple myeloma (MM) is a haematological malignancy characterized by destructive bone lesions, renal injury, anemia and hypercalcemia. Multiple myeloma is a neoplasm that often occurs in adults to the elderly. Complications of pathological fractures occur as a result of lytic lesions of the bone. Complications of MM can appear as a clinical manifestation of the patient so that further examination is needed in patients with pathological fractures to establish MM. Case: A 67-year-old female patient came to the hospital emergency room accompanied by her family in August 2022 with complaints of pain in her right thigh after falling on the homestairs. The patient has a history of heart disease and hypertension. The patient then underwent an examination and found anemia, an increase in serum creatinine and a complete fracture of the distal 1/3 of the right femur with multiple lytic lesions with decreased bone trabeculation in the skull and pelvis, clavicle, humerus, and femur bilaterally, left costae 7-8th with suspected multiple myeloma, differential diagnosis of malignant metastases and vertebral body compression 12th. Bone survey examination and sampling for histopathological examination were then carried out during the operative management of fractures with the impression of plasmacytosis so that the patient was diagnosed with Post ORIF PS, bone graft and post biopsy e.c. pathological fracture right supracondylar femur with multiple lytic lesions e.c. multiple myeloma. The patient was then referred to the orthopedic oncology department. Conclusion: Patients with pathological fracture manifestations need to be investigated further regarding the underlying cause of the condition. Multiple myeloma is one of the hematological malignancies that can cause bone lesions due to an imbalance of bone destructive factors so that it can increase the risk of pathological fracture complications. Knowing the complications, clinical manifestations and supporting characteristics of multiple myeloma can help in making the diagnosis of myeloma in patients with pathological fractures. Latar belakang: Mieloma multipel (MM) adalah keganasan hematologi yang ditandai dengan lesi tulang yang destruktif, cedera ginjal, anemia dan hiperkalsemia. Mieloma multipel merupakan neoplasma yang sering terjadi pada orang dewasa hingga lanjut usia. Komplikasi fraktur patologis terjadi akibat lesi litik pada tulang. Komplikasi MM dapat muncul sebagai manifestasi klinis pasien sehingga perlu dilakukan pemeriksaan lanjutan pada pasien fraktur patologis untuk menegakkan MM. Laporan Kasus: Pasien perempuan berusia 67 tahun datang ke IGD Rumah Sakit diantar oleh keluarganya pada Agustus 2022 dengan keluhan nyeri pada paha kanan setelah terjatuh di tangga rumah. Pasien memiliki Riwayat penyakit jantung dan hipertensi. Pasien kemudian melakukan pemeriksaan dan ditemukan kondisi anemia, peningkatan serum kreatinin dan fraktur komplit 1/3 distal os femur kanan dengan lesi litik multipel dengan penurunan trabekulasi tulang pada skull dan pelvis, os klavikula, humerus, dan femur bilateral, costae 7-8 kiri dengan suspek mieloma multipel diagnosis banding metastasis keganasan dan kompresi korpus vertebra 12. Pemeriksaan survei tulang dan pengambilan sampel untuk pemeriksaan histopatologi kemudian dilakukan saat tatalaksana operatif penanganan fraktur dengan kesan plasmasitosis sehingga pasien didiagnosis dengan Post ORIF PS dan pemasangan bone graft dan pasca biopsi e.c. pathological fracture right supracondylar femur with multiple lytic lesion e.c. multiple myeloma. Pasien kemudian dirujuk ke bagian orthopaedi onkologi. Simpulan: Pasien dengan manifestasi fraktur patologis perlu dilakukan pemeriksaan lebih lanjut mengenai penyebab yang mendasari keadaan tersebut. Mieloma multipel menjadi salah satu keganasan hematologi yang dapat menimbulkan lesi tulang akibat ketidakseimbangan faktor destruktif tulang sehingga dapat meningkatkan risiko komplikasi fraktur patologis. Mengetahui komplikasi, manifestasi klinis dan penunjang yang menjadi karakteristik dari mieloma multipel dapat membantu dalam menegakkan diagnosis mieloma pada pasien dengan fraktur patologis.